Oddziaływania poprzez nauczanie w resocjalizacji penitencjarnej - Korona, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Celem artykułu jest omówienie zagadnienia resocjalizacji poprzez naukę w warunkach izolacji więziennej, uwzględniając aktualne podstawy prawne. Skazani doceniają wartość kształcenia, jednak zapotrzebowanie na naukę w zakładzie karnym spada na rzecz rosnącej popularności kursów. Korzyści związane z kontynuowaniem nauki przemawiają za potrzebą dalszej eksploracji tego zagadnienia i podjęciem prób zminimalizowania powstałych dysproporcji, aby zapobiec dalszej marginalizacji tego ważnego środka oddziaływania na skazanych.

The aim of this paperis to discuss the issue of rehabilitation by learning in penitentiary isolation, taking into account current legal provisions. The convicts appreciate the value of learning, however the need for learning in a penitentiary institution is decreasing in favour of a growing popularity of courses. The benefits related to learning are favourable for the need of further exploration of that issue and making attempts in order to minimise the existing disproportions, in order to avoid further marginalisation of this very important means of influencing the convicts.
Influencing by Teaching in Penitentiary Rehabilitation
Keywords: nauczanie; skazany; więzienie; teaching; convicted; prison